PENERAPAN PERILAKU INOVATIF SEBAGAI PENINGKATAN KUALITAS PADA PRODUK KEMIRI OIL CELEBES - Muyardhan Muyardhan; Ibrahim Andi Indriani (STIE PGRI Dewantara Jombang, 2024)
Community Service Activities aims to improve the business performance of Kemiri Oil Celebes through digital marketing training and Human Resources capacity training for Kemiri Oil Celebes employees and managers. The Kemiri Oil Celebes Office, Central Besusu District, East Palu, carried out the activity. The fostered partner in this program is an incubator in collaboration with Tadulako University. This PKM activity was carried out intensively for approximately 2 (two) months. From the activity results, it was discovered that there was an increase in innovative behavior from training participants, which impacted increasing sales turnover and the marketing area of ​​Kemiri Oil Celebes.